Factors influencing postgraduate nursing students' study progress: A scoping review - Patricia Y. Mudzi; Nombulelo V. Sepeng (Elsevier, 2023)
Background: Universally, postgraduate nursing students' study progress is particularly concerning as this impacts completion within a prescribed minimum time. Purpose: To identify and map out the breadth of evidence available on the factors influencing postgraduate nursing students' study progress. Methods: A scoping review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for scoping reviews. Electronic databases and search engines such as ERIC, PubMed, CINAHL, MEDLINE (EBSCO), Google, and Google scholar were used. The review focused on peer-reviewed and grey literature from 2011 to 2021. Search terms were related to the factors influencing postgraduate nursing students' study progress in higher education, home, and workplace settings. Results: The search identified 1106 records from peer-reviewed and grey literature. Records that met the inclusion criteria were 26. Evidence from the review revealed six main themes that influenced the postgraduate nursing students' study progress: supervisory and peer support, work and life, funding support, research writing, geographical factors, and the structure of the postgraduate programme. Conclusion: Most literature showed that postgraduate nursing students struggled to balance work and studies therefore, employers should aim at job redesigning to ensure the working postgraduate student has time to study. Funding models that include the introduction of a student loan scheme with low interest rates payable upon graduation using revenue services may also be adopted. Postgraduate students with full-cost study funding progress better than those with no or partial-cost funding. Geographical factors were also reported to study progress in both developed and developing countries.